(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Fairy tales have played a significant role in literature throughout history, captivating readers with their enchanting narratives, timeless themes, and enduring appeal. From their origins in oral traditions to their evolution in written form, fairy tales have served as powerful vehicles for storytelling, cultural transmission, and moral instruction. Here are some theoretical perspectives on the role of fairy tales in literature